The impact of vertical centrifugation on olive oil quality. Issue 3 (9th September 2016) - Guerrini, Lorenzo; Luca Pantani, Ottorino; Parenti, Alessandro
Abstract: Vertical centrifugation is an important step in continuous virgin olive oil production. It is used to clarify the oil, through the separation of water and suspended solids. Despite its effectiveness, the centrifuge can impair quality. In particular, it requires water to work, which reduces the concentration of minor compounds in the oil, and introduces dissolved oxygen. This paper reports the impact of the use of a vertical centrifuge on olive oil quality, with particular respect to minor compounds. Tests were carried out on two common cultivars ( Arbequina and Coratina ) 1 month after production and after six months of storage. The vertical centrifuge was found to impair parameters related to oxidation, such as peroxide value and K232. Particularly, the vertical centrifuge was able to increase the peroxide number of about 2 meq O2 /kg. In addition, it oxidizes phenols and consequently reduces the ratio of oxidized and nonoxidized forms of secoiridoids. Furthermore, it removes both hydrophobic (i.e., roughly 25 mg/kg of tocopherols was removed) and hydrophilic antioxidants (biophenolic compounds). Phenols are removed as a function of the oil/water partition coefficient. A total phenols decrease of 47 mg/kg in Arbequina and 117 mg/kg in Coratina was due to vertical centrifugation. Finally, the vertical centrifuge oxidizes the oils and led to the detection of the rancid defect after six months of storage by an olive oil sensory panel group. Practical applications: The use of the vertical centrifuge in VOO production is a debated issue. In fact, despite some producers recently started to avoid vertical centrifugation for their top quality products. However, vertical centrifugation is a fundamental step in VOO production, and little is still known on the influence of this centrifuge on VOO quality.